2017
DOI: 10.1016/j.it.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

THEMIS: Two Models, Different Thresholds

Abstract: THEMIS, a recently identified T-lineage restricted protein, is the founding member of a large metazoan protein family. Gene inactivation studies have revealed a critical requirement for THEMIS during thymocyte positive selection, implicating THEMIS in signaling downstream of the T cell antigen receptor (TCR); but the mechanistic underpinnings of THEMIS’ function have remained elusive. A previous model posited that THEMIS prevents thymocytes from inappropriately crossing the positive/negative selection threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Interestingly, all eleven genes correlated with low self-reactivity, particularly at the early DP stage of development. This included Themis (Figure 6-figure supplement 2b), which encodes a protein required for modulating TCR signaling during positive selection (Lesourne et al 2009;Patrick et al 2009;Kakugawa et al 2009;Fu et al 2009;Johnson et al 2009;Choi, Warzecha, et al 2017;Choi, Cornall, et al 2017;Mehta et al 2018). Moreover, expression of the curated set of ion channel genes in the ImmGen microarray data set revealed that group 2 genes, whose expression correlated with low self-reactivity, also displayed higher expression in preselection wildtype thymocytes (Figure 6-figure supplement 2c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all eleven genes correlated with low self-reactivity, particularly at the early DP stage of development. This included Themis (Figure 6-figure supplement 2b), which encodes a protein required for modulating TCR signaling during positive selection (Lesourne et al 2009;Patrick et al 2009;Kakugawa et al 2009;Fu et al 2009;Johnson et al 2009;Choi, Warzecha, et al 2017;Choi, Cornall, et al 2017;Mehta et al 2018). Moreover, expression of the curated set of ion channel genes in the ImmGen microarray data set revealed that group 2 genes, whose expression correlated with low self-reactivity, also displayed higher expression in preselection wildtype thymocytes (Figure 6-figure supplement 2c).…”
Section: Resultsmentioning
confidence: 99%
“…A number of molecules have been identified which are involved in modulating TCR signaling in DP thymocytes, and which are downregulated during positive selection. These include the microRNA miR-181a: which enhances TCR signaling by downregulating a set of protein phosphatases (Li et al 2007), Tespa1: a protein that enhances calcium release from the ER (Lyu et al 2019;Liang et al 2017), components of a voltage gated sodium channel (VGSC): that prolongs calcium flux via an unknown mechanism (Lo, Donermeyer, and Allen 2012), and Themis: a TCR associated protein with controversial function (Kakugawa et al 2009;Patrick et al 2009;Lesourne et al 2009;Johnson et al 2009;Fu et al 2009;Choi, Cornall, et al 2017;Fu et al 2013;Choi, Warzecha, et al 2017;Mehta et al 2018). While a diverse set of potential players have been identified, a clear understanding of the mechanisms that render preselection DP thymocytes sensitive to low affinity self-ligands remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of SHP-1 activity has been proposed to be the key mechanism of action of Themis, a modulator of TCR signal strength predominantly expressed in DP thymocytes [ 19 , 20 ]. However, it remains controversial whether Themis inhibits or promotes SHP-1 activity [ 19 , 21 ]. Taken together, in thymocytes, the TCR converts signals elicited by pMHC ligands with a continuum of affinities to a digital outcome of positive selection or clonal deletion.…”
Section: Introductionmentioning
confidence: 99%
“…This differential is thought to enable positive selection from low affinity/avidity interactions, prevent the same contacts from activating mature ab T cells, and provide a "safety net" for negative selection to more effectively suppress autoimmunity (6)(7)(8)(9). Although the T lineage-specific Themis protein contributes to this differential in TCR sensitivity between immature and mature ab T cells (9,15,16), the precise mechanisms by which this protein and possibly additional factors "tune" TCR signaling and control ab TCR selection remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%